Effect of local somatosensory stimulus on postural sway during sit-to-stand movement in the elderly - Peter Annor (BMC, 2021)
Abstract Background Sit-to-stand (STS) is a complex movement that requires successful postural control. Aging is a normal part of human life that leads to weakness of sensory capabilities, resulting in diminished postural control. Therefore, STS movement is a challenging task for the elderly. Local tendon vibration (LTV) can be utilized to assist STS of the elderly by improving postural control. Many studies have revealed that the LTV has various physiological positive effect. However, previous studies did not consider subjects’ individual difference for properties of applied LTV. Also, there are almost no studies to assist and to improve elder’s STS movement. Thus, the purpose of this study was to examine the influence of lower limb LTV on postural sway during STS in the elderly, and to examine whether a specific vibration frequency can increase postural control in the elderly. Results The common characteristic differences between the elderly and younger population during STS movement were analyzed. In addition, the effect of vibration on the center of mass (COM) and the center of pressure (COP) variable responses in young adults and the elderly were investigated. As a result, the elderly exhibit larger COP sway area and higher COP mediolateral (ML) displacement than the young adults. In addition, the elderly generally have lower COM velocities in all directions compared to the young adults. It was found that COP and COM related to postural stability are affected when LTV of the 180 Hz, 190 Hz and 250 Hz is applied to the elderly. Particularly, the 190 Hz vibration induced significant reduction in COP sway area and COP ML displacement. Conclusions These results mean that the LTV contributes to stability of elders’ STS movement by reducing postural sway. Furthermore, a reduction of postural sway depends on frequency of the LTV. These findings suggest that individual response to characteristics of vibration must be considered, and imply that the LTV can be used as rehabilitation therapy to improve postural control in the elderly, and utilized in motion assistive devices to deliver apt vibration frequencies. Trial registration CRIS, KCT0005434 , Registered 25 September 2020, Retrospectively registered, https://cris.nih.go.kr/cris/index/index.do